LANGUAGE STYLE USED IN BEAUTY PRODUCT ADVERTISEMENTS OF “GADIS” MAGAZINE - MARDIANA, PUTRI (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keyword: Language style, language style in advertisement, GADIS magazine.People may use different language style when delivering ideas through language. The way people speak depends on the speaker’s relationship with the addressee in determining the appropriate style of speaking used. In conducting the study, the writer analyzed two problems of study namely; (1)What kinds of language style are used in the slogan of advertisement of beauty products in GADIS magazine seen from its sentence structure? (2)What types of language style are used in the promotional sentences of beauty product advertisement of GADIS magazine?This study used qualitative approach and document analysis since the analysis focused on analyzing and interpreting the text in the form of slogans and promotional sentences.The theory used in this study is the language style theory proposed by Keraf (2010) and Wells (1995).From 15 slogans analyzed, the writer found all of the type of language style based on sentence structure. The parallelism style is mostly used and the occurrence is about 6 times, it is followed by climax style found in 5 slogans and anticlimax found 2 times, the next is repetition style and antithesis style occurs only once in each type. Based on types of language style in advertisement, from 28 Promotional, the writer found 14data which are categorized into demonstration style, 8 data are categorized into hard sell style, 3 data are categorized into problem – solution style, 2 data are categorized into spokesperson style and one data categorized into comparison style.In conclusion, the writer concludes that in parallelism style and demonstration style the creators of the advertisement mostly used adjectives from the vocabulary of the sentence. Finally, the writer concludes that adjectives are important in advertising to add prestige and desirability for the readers. For further research, the researcher are expected to be able to develop and explore further using different theory and different subject such as advertisement in radio in order to help the readers to understand more about theory of language style.